A national randomized controlled trial of the impact of public Montessori preschool at the end of kindergarten - Angeline S. Lillard; David Loeb; Juliette Berg; Maya Escueta; Karen Manship; Alison Hauser; Emily D. Daggett (Proceedings of the National Academy of Sciences, 2025)
Although seminal studies from the early 1960s suggested quality preschool can have lasting positive effects, agreement is lacking on the efficacy of different preschool models. The Montessori model is longstanding but lacks rigorous impact studies; prior random lottery studies included just one or two schools, among other compromises. Here, we report on end-of-kindergarten (age 5 to 6) impacts from a national study of public Montessori preschool. We compared children offered a Montessori seat via competitive lottery admission processes at one of 24 public Montessori schools at age 3 ( n = 242 ) to children not offered a seat ( n = 346 ), estimating Montessori impacts with intention-to-treat and complier average causal effect models. Roughly half of the treatment sample still attended Montessori for kindergarten. Although there were no notable impacts at the end of PK3 or PK4, at the end of kindergarten, controlling for baseline scores and demographics, Montessori children had significantly higher reading, short-term memory, theory of mind, and executive function scores. Intention-to-treat effect sizes exceeded a fifth of a SD, considered large in field-based school research [M. A. Kraft, Educ. Res. 49 , 241–253 (2020)]. This contrasts sharply with the more typical finding, where impacts of preschool are observed immediately following the program but disappear by the end of kindergarten. Further, a cost analysis suggested three years of public Montessori preschool costs less per child than traditional programs, largely due to Montessori having higher child:teacher ratios in PK3 and PK4. Although sensitivity and robustness analyses yielded similar results, important limitations of the study should be noted.